THE EMPOWERING THE YOUNG GENERATION THROUGH THE TOURISM AMBASSADOR COMPETITION TO ENHANCE THE TOURISM SECTOR AND STIMULATE NEW ECONOMIC GROWTH IN LEBAK REGENCY - Nidaan Khofiya; Salsha Awalia; Ari Apriyansa (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2025)
The tourism sector plays a crucial role in Indonesia's economy, including in Lebak Regency. Despite its abundant natural and cultural tourism potential, this sector has yet to be fully optimized. One effective strategy to strengthen the tourism sector is by engaging the younger generation in the development and promotion of tourist destinations. The Tourism Ambassador Competition serves as an effective means to cultivate a generation that is both aware of and capable of promoting their region’s tourism potential. This study aims to analyze the role of the Tourism Ambassador Competition in youth empowerment and its impact on tourism sector growth and new economic revival in Lebak Regency. This research employs a qualitative approach using a case study method. Data were collected through interviews with competition organizers, Tourism Ambassador participants, and local communities. Additionally, observations of competition activities were conducted to obtain a more comprehensive understanding. The findings indicate that the Tourism Ambassador Competition has positively influenced young people's awareness and involvement in the tourism sector. Participants not only develop communication and promotional skills but also act as change agents in introducing local tourist destinations. Furthermore, the presence of Tourism Ambassadors contributes to local economic growth by increasing the number of visitors. The Tourism Ambassador Competition has proven to be an effective initiative in strengthening the role of the younger generation as pioneers in revitalizing tourism in Lebak Regency. Through capacity-building efforts for participants, the tourism sector can expand more rapidly, create new economic opportunities, and enhance the well-being of local communities.